GANGGUAN BELAJAR MENULIS PADA ANAK DISGRAFIA (STUDI KASUS PADA ANAK KELAS III SD) - Roza Muchtar; Agustina Agustina (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2022)
The purpose of this research were to 1) describe the learning (writing) disorder experienced by Aini, 2) describe the type of learning (writing) disorder experienced by Aini, and 3) describe the way to overcome Aini's writing disorder. The type of research used is qualitative research with descriptive methods and case study approaches. The data source of this research is Nur Aini Deswita. Data collection techniques in this study are documentation and interview techniques. The data were analyzed in three stages, namely data collection, data reduction, and drawing conclusions and data verification. The results of this study indicate that Aini's writing learning disorder (dysgraphia) includes inconsistent spacing between letters, lots of scribbles in writing and inconsistent font size, unfinished occurrence, not following proper and proportional lines when writing. The types of writing disorders (dysgraphia) experienced by Aini are dyslexia dysgraphia and spatial dysgraphia. For learning writing disorder (dysgraphia) experienced by Aini, writing learning strategies can be given including, pre-writing activity strategies, tracing letters, writing block letters, and writing in cursive.